Power Speed Profile: Performance model for road cycling (1) - van Bon, M.; Vroemen, G. (2018)
In road cycling aerobic efforts are often used as a benchmark for performance. However, road cycling is more than just an aerobic endurance effort. The outcome of a race is often decided during critical periods, for example when riders try to break-away form the others or in a final sprint. It is therefore important to know how well a rider performs during these critical periods. In a series of two articles we examined which critical periods are representative for road cycling performance. We also examined how these performances can be measured and compared with each other. In Part I three Power Profile tests are compared: the test of Allen & Coggan, of the Australian Institute of Sports and of the World Cycling Center. In part II, the newly developed Power Speed Profile performance model (with related test) is introduced. Evaluate the results of your test with our free tool: powerspeedprofile.com.